Modelling of delamination in composite shells under different temperature conditions - Soman, Rohan Nandkishor; Ostachowicz, Wieslaw (Computer Assisted Methods in Engineering and Science, 2017)
Composite shells and panels are widely used in aerospace structures. These are often subjected to defects and damage from both in-service and manufacturing events. Delamination is the most important damage defect. This paper deals with the computational modelling of delamination in laminated composite shells. The use of three-dimensional finite elements for determining delamination of these structures is computationally expensive. Here combined double-layer and single-layer shell elements are employed to study the effect of delamination on the strain values in the sample under purely bending loads. The computational load and the accuracy of the modelling approaches are compared. It is shown that a through-the-thickness delamination can be modeled and analyzed effectively without requiring a great deal of computing time and memory. Some of the results are compared with the experimental results.